Duševno zdravje visoko izobraženih migrantk - Verderber, Sara (Socialno delo, 2023)
Research on migration through the prism of gender and higher education, and in relation to mental health, is rare. Migration trajectories are fraught with many stressors and barriers of the new environment, which in turn directly or indirectly affects the quality of mental health and thus the successful integration of migrant women into the new community. In the article, the micro-level migration process of migrant women with higher education is described, and how it affects their mental health. The primary method was narrative interviews with the supporting methods of an ethnographic diary and a demographic questionnaire. The sampling was carried out using the snowball sampling method. The study included 36 subjects from the Netherlands, Germany and Slovenia. In the context of social work and migration, this is an important contribution to a better understanding of the daily lives of migrant women and thus the state of their mental health. This in turn leads to social justice in the form of cultural, social and socio-political sensitivity and support to improve the mental health of migrants.
Keywords: depresija; depression; integracija; integration; migracije; migration; social isolation; socialna izolacija; stres; stress